DNA ploidy in Salix retusa agg. only partly in line with its morphology and taxonomy. (19th July 2019) - Kosiński, Piotr; Sliwinska, Elwira; Hilpold, Andreas; Boratyński, Adam
Abstract : Salix retusa agg. encompasses small, prostrate willows occurring in the subalpine and alpine zones of European mountains. Karyological relationships among taxa in this group remain unclear. In this study, DNA ploidy was estimated using flow cytometry of silica‐dried specimens, covering the entire distribution area of the species. As a result, the presence of two main lineages was revealed: the exclusively diploid S. serpillifolia and the predominantly octoploid S. retusa s.l. Only at the western and eastern limits of the distributional range of the latter species different levels of DNA ploidy occurred: hexaploidy in the western Pyrenees, and up to decaploidy in the southern Carpathians. These results were compared with leaf morphology analyses presented in the work of Kosiński et al. (2017). In the western Pyrenean populations, the lower ploidy corresponded to smaller leaf sizes as compared to other populations of S. retusa s.l. The elevated ploidy in the southern Carpathian populations did not translate into bigger dimensions of plants in this area. However, the populations from the northern part of the Carpathian arc, distinguished by larger leaves and sometimes considered as a distinct taxon ( S. kitaibeliana ), consisted mainly of octoploid individuals. Thus, DNA ploidy estimations did not confirm the separate taxonomic status of S. kitaibeliana .